FOFIFA 190, high yielding irrigated lowland variety, released for irrigated lowlands in Madagascar - CGIAR Research Program on Rice (2021)
Old Varieties dominate the rice fields of Madagascar. However, in 2019 four new irrigated lowland rice varieties were released including FOFIFA 190.